Blood Pressure and Intracranial Aneurysms in Autosomal Dominant Polycystic Kidney Disease - Mariusz Niemczyk; Tomasz Pilecki; Monika Gradzik; Maciej Bujko; Stanisław Niemczyk; Leszek Pączek (Karger Publishers, 2014)
Background/Aims: Autosomal dominant polycystic kidney disease (ADPKD) is correlated with an increased frequency of both intracranial aneurysms (ICANs), and arterial hypertension (AH). The aim of our study was to search for the association between blood pressure (BP) and ICANs in ADPKD patients. Methods: Sixty-eight adult, pre-dialysis phase ADPKD patients underwent both screening for ICANs with magnetic resonance angiography of the brain, and ambulatory blood pressure monitoring (ABPM). Results: ICANs were diagnosed in 10 patients (ICAN(+) group), while in 58 were not (ICAN(-) group). The nighttime maximum diastolic blood pressure (DBP), maximum increase in DBP from measurement to measurement (positive delta of DBP) at night, and the standard deviation of the daytime mean arterial pressure were significantly higher in ICAN(+) compared to ICAN(-) patients. Additionally, in a subgroup of patients after 45 years-of-age, ICAN(+) patients had significantly higher maximum 24-hour and daytime systolic blood pressure, maximum 24-hour, daytime, nighttime DBP, maximum daytime and nighttime positive delta of DBP compared to ICAN(-) cases. Conclusions: Development of ICANs in hypertensive ADPKD patients is accompanied with higher values of some BP parameters measured by ABPM. Hypertensive ADPKD patients with substantial fluctuations in BP assessed by ABPM, especially those after 45 years-of-age, should become candidates for screening for ICANs.